Belief Propagation based Scheduling for Energy Efficient Multi-drone Monitoring System - Jung, Soyi; Yang, Peng; Quek, Tony Q.S.; Kim, Jae Hyun (International Conference on ICT Convergence, 2020)
A state-of-the-art commercial drones have typically battery limitations to support their operation. Effective battery management is one of the main enablers of practical drone system operations. This paper designs an energy-efficient monitoring drone-based scheduling algorithm to control the number of activation drones in a multi-drone system. This study focuses on reducing overlapping regions of the inter-drone monitoring area in terms of energy efficiency. We formulate this problem as finding a maximum weight independent set (MWIS) problem on a graph model and propose a real-time update of the message algorithm based on belief propagation. Our results showed that the proposed algorithm achieves significant improvements in energy consumption compared to the existing algorithm.
Keywords: Battery Management; Belief propagation; Energy efficient; Maximum weight independent sets (MWIS); Monitoring system; Overlapping regions; Real-time updates; State of the art; Belief propagation; Drone; Energy-efficiency; Maximum independent set; Monitoring drone